The role of food and nutrition in the prevention and pathogenesis of atherosclerosis development - Stępnik, Jolanta; Stępnik, Konrad; de Pourbaix, Renata; Maj-Gnat, Katarzyna; Wołoszynek, Eliza; Bujak-Krzemińska, Agata (Journal of Education, Health and Sport, 2019)
Nowadays it is known that atherosclerotic changes in the arteries occur very early. Occur in practically the entire population of western civilization countries and show rapid progression over the years. As a result of chronic inflammatory process, which lasts even several dozen years, the developing atherosclerosis gradually destroys all layers of the arterials walls. Studies indicate that two diets recommended for atherosclerosis prevention and treatment are the DASCH diet (Dietary Approaches to Stop Hypertension), especially in relation to blood pressure control, and the Mediterranean diet. In the treatment of atherosclerosis, it is extremely important to exclude factors that increase the risk of this disease. It is important to emphasize that the conversion of energy consumed from fats to that from simple carbohydrates results in reduction of HDL C (high density lipoproteins cholesterol) concentration.